2021
DOI: 10.1007/s11517-021-02469-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic OCT data in challenging conditions: three-dimensional OCT and presence of abnormalities

Abstract: Nowadays, retinal optical coherence tomography (OCT) plays an important role in ophthalmology and automatic analysis of the OCT is of real importance: image denoising facilitates a better diagnosis and image segmentation and classification are undeniably critical in treatment evaluation. Synthetic OCT was recently considered to provide a benchmark for quantitative comparison of automatic algorithms and to be utilized in the training stage of novel solutions based on deep learning. Due to complicated data struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Figure 3 shows examples of the synthesized layer boundaries for each of the classes (HC, MS, and NMO). As we focus on retinal thickness maps because of their usefulness as biomarkers for neurologic diseases, it is not necessary to create synthetic textures in order to generate a full OCT image, as we did in Danesh et al 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows examples of the synthesized layer boundaries for each of the classes (HC, MS, and NMO). As we focus on retinal thickness maps because of their usefulness as biomarkers for neurologic diseases, it is not necessary to create synthetic textures in order to generate a full OCT image, as we did in Danesh et al 24 …”
Section: Methodsmentioning
confidence: 99%
“…The construction of synthetic OCT data has been considered by researchers over the past few years. 19 – 22 In recent work, 23 , 24 we used an active shape model (ASM 25 ) to construct synthetic two-dimensional (2D) and three-dimensional (3D) OCT data in the macular region. In this article, we use that model as an augmentation method to generate synthetic 3D OCT boundaries of the macular region from healthy controls (HCs) and patients with MS and NMO.…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography (OCT), as a non-invasive optical imaging technique, has been rapidly developed during the last decades 6 . OCT has strong tissue penetration, contains stereoscopic imaging, and provides more details of the lesions, thereby supporting the quantification of the lesions directly 7 . Based on OCT images, researchers have proposed a number of predictors of MH surgical efficacy 8 .…”
Section: Background and Summarymentioning
confidence: 98%
“…This synthetic data aids in training vessel segmentation algorithms without the need for manual annotation. Danesh et al 33 proposed a method that used the Active Shape Model with a limited number of OCT images for training to create synthetic OCTs, delineate retinal boundaries, and point to abnormalities. The comparison of thickness maps showed that the synthetic dataset can be used as a statistically acceptable representative of the original dataset, suggesting that the proposed algorithm provided an augmentation method for OCT scans.…”
Section: Sharing Datasets Securelymentioning
confidence: 99%